1985
DOI: 10.1083/jcb.100.6.1848
|View full text |Cite
|
Sign up to set email alerts
|

Binding of laminin to type IV collagen: a morphological study.

Abstract: A mixture of laminin and type IV collagen was analyzed by rotary shadowing using carbon/platinum and electron microscopy. Laminin was found to form distinct complexes with type IV collagen: one site of interaction is located 140 nm from the COOH-terminal, noncollagenous (NC1) domain and the other is located within the NH2-terminal region. The isolated NC1 fragment of type IV collagen does not appear to interact with laminin, while pepsin-treated type IV collagen, which lacks the NC1 domain, retains its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(71 citation statements)
references
References 22 publications
4
67
0
Order By: Relevance
“…Self-assembly of type IV collagen can also proceed laterally via its triple helical regions or via binding of the non-collagenous domain to the triple helical region of another molecule to form multimers (27,29). Studies examining the interaction of laminin and heparin with type IV collagen demonstrated that both molecules show significant binding to the triple helical region of type IV collagen (28,30). Since SAP binding to type IV collagen is most likely via type IV collagen's triple helical region, it may modify the assembly of type IV collagen or its interaction with proteoglycans and laminin and alter the structure of the basement membrane and its function.…”
Section: Fig 7 Effect Of Camentioning
confidence: 99%
“…Self-assembly of type IV collagen can also proceed laterally via its triple helical regions or via binding of the non-collagenous domain to the triple helical region of another molecule to form multimers (27,29). Studies examining the interaction of laminin and heparin with type IV collagen demonstrated that both molecules show significant binding to the triple helical region of type IV collagen (28,30). Since SAP binding to type IV collagen is most likely via type IV collagen's triple helical region, it may modify the assembly of type IV collagen or its interaction with proteoglycans and laminin and alter the structure of the basement membrane and its function.…”
Section: Fig 7 Effect Of Camentioning
confidence: 99%
“…There is evidence that the latter are distributed in most basement membranes (4,5). Type IV collagen not only forms the main structural framework of all basement membranes, but also serves as scaffolding for the binding of other basement membrane components (7,8). One important function of type IV collagen is its ability to promote the adhesion and motility of various normal and transformed cell types (9).…”
mentioning
confidence: 99%
“…This collagen is unique to basement membrane and forms large open or polygonal networks [31,32]. This network forms a scaffolding to which other proteins bind at specific sites [33][34][35]. Entactin is involved in the binding of laminin to collagen type IV [36].…”
Section: Discussionmentioning
confidence: 99%